Power storage device
The power storage device employs a structured solid electrolyte layer with a dense and porous layer configuration to prevent cracking and enhance capacity by minimizing stress and shrinkage differences during sintering.
Patent Information
- Application Number
- JP2023150579
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-28
AI Technical Summary
The existing solid electrolyte structure for all-solid-state batteries can suffer from cracks at the interface between the dense and porous layers during sintering, leading to a decrease in the capacity of the power storage device.
A power storage device configuration that includes a solid electrolyte layer with a dense layer and a porous layer, where the porous layer is structured with a first porous layer in contact with the dense layer and a second porous layer with even higher porosity, reducing the stress and shrinkage differences between layers during sintering.
This configuration effectively suppresses the occurrence of cracks and increases the capacity of the power storage device by reducing internal resistance and facilitating the formation of a conductor within the porous layer.
Smart Images

Figure 2025043193000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electricity storage device, and more particularly to an electricity storage device including a solid electrolyte layer. [Background technology]
[0002] 2. Description of the Related Art In recent years, all-solid-state batteries having a solid electrolyte interposed between electrodes have been considered as electricity storage devices used as batteries for automobiles and electronic devices, from the viewpoint of improving safety and heat resistance.
[0003] Patent Document 1 discloses a solid electrolyte structure for an all-solid-state battery, which includes a plate-shaped dense body made of ceramics containing a solid electrolyte, and a porous layer made of ceramics containing the same or different solid electrolyte as the solid electrolyte of the dense body and formed by firing and integrating at least one surface of the dense body. Such a solid electrolyte structure can be formed, for example, by firing a first molded body obtained by molding a first ceramic material containing a solid electrolyte into a plate shape to form a dense body, and then applying a second ceramic material to be a porous layer on at least one surface of the dense body to form a second molded body, which is then fired at a temperature lower than the firing temperature of the dense body. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2008 / 059987 Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the solid electrolyte structure of Patent Document 1, when the dense layer and the porous layer are simultaneously fired to produce an integrally sintered solid electrolyte, cracks may occur at the interface between them, and the capacity of the manufactured electricity storage device may decrease due to these cracks.
[0006] An object of the present disclosure is to provide an electricity storage device capable of suppressing the occurrence of cracks and increasing the capacity. [Means for solving the problem]
[0007] An electric storage device according to one embodiment of the present disclosure is an electric storage device including a first electrode, a second electrode, a solid electrolyte layer including a solid electrolyte and disposed between the first electrode and the second electrode, and a conductor disposed in the solid electrolyte layer. The solid electrolyte layer has a dense layer and a porous layer disposed between the dense layer and at least one of the first electrode and the second electrode. The porous layer includes a first porous layer in contact with the dense layer and having a porosity higher than that of the dense layer, and a second porous layer in contact with the first porous layer and having a porosity higher than that of the first porous layer. Effect of the Invention
[0008] According to the present disclosure, it is possible to provide an electricity storage device capable of suppressing the occurrence of cracks and increasing the capacity. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view of an electricity storage device according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] 1. Overview The electricity storage device 1 according to the embodiment of the present disclosure will be described in detail with reference to the drawings. Note that the embodiment described below is merely an example of the present disclosure, and the present disclosure is not limited to this embodiment. Other than this embodiment, various modifications are possible according to the design, etc., as long as they do not deviate from the technical idea of the present disclosure. In addition, the following embodiments may be realized in appropriate combination.
[0011] Hereinafter, an overview of the electricity storage device 1 will be described with reference to Fig. 1. Note that the drawings described in the following embodiments are schematic drawings, and the ratios of sizes and thicknesses of the components in the drawings do not necessarily reflect the actual dimensional ratios.
[0012] As shown in FIG. 1, the electricity storage device 1 includes a first electrode 11, a second electrode 12, a solid electrolyte layer 20, and a conductor (hereinafter, also referred to as conductor X). The conductor X is disposed in the solid electrolyte layer 20. The solid electrolyte layer 20 includes a solid electrolyte (hereinafter, also referred to as solid electrolyte Y). The solid electrolyte layer 20 includes a dense layer 30 and a porous layer 40. The porous layer 40 is disposed between the dense layer 30 and at least one of the first electrode 11 and the second electrode 12. The porous layer 40 includes a first porous layer 41 and a second porous layer 42. The first porous layer 41 is in contact with the dense layer 30 and has a porosity higher than that of the dense layer 30. The second porous layer 42 is in contact with the first porous layer 41 and has a porosity higher than that of the first porous layer 41.
[0013] According to the electricity storage device 1 of the present embodiment, it is possible to suppress the occurrence of cracks and increase the capacity. The reason why the electricity storage device 1 has the above-mentioned configuration and thus exhibits the above-mentioned effects can be inferred, for example, as follows. The electricity storage device 1 of the present embodiment is a capacitor in which a capacitance is generated by an electric double layer at the contact interface between the conductor X and the solid electrolyte Y. In the electricity storage device 1, a first porous layer 41 having a porosity higher than that of the dense layer 30 is arranged in contact with one or both sides of the dense layer 30, and a second porous layer 42 having a porosity higher than that of the first porous layer 41 is arranged in contact with the side of the first porous layer 41 opposite to the dense layer 30. In this way, in the electricity storage device 1, the porous layer 40 has a gradient in which the porosity increases stepwise in the thickness direction and toward the outside of the electricity storage device 1, thereby reducing the change in porosity between layers, and increasing the porosity on the surface side of the solid electrolyte layer 20, thereby making it easier for the conductor X to be formed in the pores of the pores by impregnation. By adopting such a structure, the difference in shrinkage behavior at the interface between layers with different porosities during sintering is reduced, and stress during integral sintering is alleviated, so that it is considered that the occurrence of cracks can be reduced even when the dense layer 30 and the porous layer 40 are integrally fired. Therefore, it is possible to further reduce the DCR (Direct Current Resistance), which is the internal resistance. In addition, by suppressing the occurrence of such cracks and, in addition, making it easier for the conductor X to be formed, it is possible to increase, for example, the contact area between the conductor X and the solid electrolyte Y, and further, by discontinuously changing the porosity in the thickness direction, it is possible to increase the thickness of the outermost layer with the highest porosity, which is considered to increase the capacity of the electricity storage device 1.
[0014] 2.Details <Electricity storage device> 1, the electricity storage device 1 includes a first electrode 11, a second electrode 12, and a solid electrolyte layer 20. The solid electrolyte layer 20 includes a dense layer 30 and a porous layer 40. The porous layer 40 includes a first porous layer 41 and a second porous layer 42. Each component will be described below.
[0015] [electrode] The electricity storage device 1 has a first electrode 11 and a second electrode 12 on either side of a solid electrolyte layer 20 as a pair of electrodes functioning as current collectors for the positive and negative electrodes.
[0016] The first electrode 11 and the second electrode 12 are formed of a metal such as copper, silver, gold, iron, nickel, etc. The first electrode 11 and the second electrode 12 are, for example, circular with a diameter of about 10 mm and a thickness of about 0.5 μm.
[0017] The first electrode 11 and the second electrode 12 can be formed on both sides of the solid electrolyte layer 20 by, for example, a sputtering method.
[0018] [Solid electrolyte layer] The solid electrolyte layer 20 is disposed between the first electrode 11 and the second electrode 12. The solid electrolyte layer 20 contains a solid electrolyte Y. That is, the dense layer 30, the first porous layer 41, and the second porous layer 42 that constitute the solid electrolyte layer 20 contain the solid electrolyte Y.
[0019] As the solid electrolyte Y, for example, Li 1.3 Al 0.3 Ti 1.7 A Li-ion conductor such as (PO4)3(LATP) can be preferably used. By using a Li-ion conductor as the solid electrolyte Y, it is possible to form an all-solid-state capacitor in which lithium ions near the electrode surface move to form an electric double layer.
[0020] [conductor] The conductor X is disposed in the solid electrolyte layer 20. The conductor X is usually formed and disposed in the pores (voids) of the first porous layer 41 and the second porous layer 42 constituting the porous layer 40. A conductive material containing carbon is preferably used as the conductor X. The conductive material containing carbon allows conductive particles with improved dispersibility to be disposed in the pores of the porous layer 40, thereby further increasing the capacity of the electricity storage device 1. The conductive material containing carbon can be formed, for example, by carbonizing a polyimide solution, or by impregnating with a dispersion of carbon powder.
[0021] The solid electrolyte layer 20 includes a dense layer 30 and a porous layer 40 .
[0022] (Dense layer) The solid electrolyte layer 20 has one dense layer 30. The dense layer 30 is, for example, circular with a diameter of about 10 mm in plan view, and the dense layer 30 has a thickness of, for example, about 0.5 mm.
[0023] The term "dense layer" refers to a layer having a small porosity. The porosity of the dense layer 30 is smaller than that of the porous layer 40 (the first porous layer 41 and the second porous layer 42). The term "porosity" refers to the ratio of the total volume of the pores (voids) to the volume of the dense layer 30, the first porous layer 41, or the second porous layer 42, expressed as a percentage. The pores (voids) are preferably interconnected pores, but may partially include single pores. The electricity storage device 1 is formed by disposing a conductor in the pores (voids) in the dense layer 30, the first porous layer 41, and the second porous layer 42. The porosity of the dense layer 30, the first porous layer 41, and the second porous layer 42 can be measured by the Archimedes method, the weight porosity method, or the like. The porosity of the dense layer 30, the first porous layer 41 and the second porous layer 42 can be adjusted, for example, by changing the amount of a resin component, such as cross-linked polymethyl methacrylate, that decomposes thermally during firing to form pores when each layer is formed.
[0024] The porosity of each of the dense layer 30, the first porous layer 41, and the second porous layer 42 may be constant in the thickness direction or may vary in the thickness direction. The porosity of the dense layer 30, the first porous layer 41, and the second porous layer 42 means the average porosity of each layer.
[0025] The porosity of the dense layer 30 is, for example, 10% or less. In this case, conduction of the conductor X in the dense layer 30 can be suppressed, and the electricity storage device 1 can be prevented from failing to function as a capacitor. The porosity of the dense layer 30 is preferably 9% or less, and more preferably 8% or less. The smaller the porosity of the dense layer 30, the more preferable it is, and it may be 0%.
[0026] (porous layer) The solid electrolyte layer 20 has a porous layer 40 on one or both sides in contact with one dense layer 30. In the pores of the porous layer 40, a conductor X is disposed.
[0027] The porous layer 40 includes a first porous layer 41 and a second porous layer 42. The porous layer 40 may be composed of only the first porous layer 41 and the second porous layer 42, or may further include, in addition to the first porous layer 41 and the second porous layer 42, another porous layer such as a third porous layer that is in contact with the second porous layer and has a porosity greater than that of the second porous layer.
[0028] (1st porous layer) The first porous layer 41 is disposed in contact with the dense layer 30. The first porous layer 41 may be disposed on one side of the dense layer 30, or on both sides.
[0029] The porosity of the first porous layer 41 is greater than the porosity of the dense layer 30 .
[0030] The porosity of the first porous layer 41 is preferably 5% to 20%, more preferably 8% to 20%, and even more preferably 10% to 20%. In this case, the difference in porosity between the layers can be made smaller, and the occurrence of cracks can be further suppressed.
[0031] The thickness of the first porous layer 41 is preferably 100 μm or more and 2000 μm or less, and more preferably 200 μm or more and 400 μm or less. In this case, the DCR of the electricity storage device 1 can be further reduced.
[0032] (2nd porous layer) The second porous layer 42 is disposed in contact with the first porous layer 41. The porosity of the second porous layer 42 is greater than the porosity of the first porous layer 41.
[0033] The porosity of the second porous layer 42 is preferably 10% or more and 50% or less, more preferably 15% or more and 45% or less, and even more preferably 20% or more and 40% or less. In this case, it is possible to achieve both the ease of forming the conductor X by impregnation and the strength of the second porous layer 42, and as a result, the capacity of the electricity storage device 1 can be further increased.
[0034] The thickness of the second porous layer 42 is preferably 100 μm or more and 2000 μm or less, and more preferably 300 μm or more and 500 μm or less. In this case, the thickness of the portion with high porosity can be increased, and as a result, the capacity of the electricity storage device 1 can be further increased.
[0035] The thickness of the second porous layer 42 is preferably greater than the thickness of the first porous layer 41. In this case, the thickness of the portion with high porosity can be made greater, and as a result, the capacity of the electricity storage device 1 can be increased.
[0036] <Method of manufacturing electricity storage device> The electricity storage device 1 can be produced by, for example, a production method including the following steps of raw material preparation, molding, firing, impregnation, re-firing, and current collector formation.
[0037] [Raw material preparation process] In this step, the raw materials for forming the dense layer, the first porous layer, and the second porous layer are each 1.3 Al 0.3 Ti1.7 It is prepared by adding a component that volatilizes when heated to form pores, such as cross-linked polymethylmethacrylate, to a powder of a solid electrolyte such as (PO4)3(LATP), and mixing. This raw material may also contain a sintering aid such as Li3PO4, an organic binder such as polyvinyl alcohol, and the like.
[0038] [Molding process] In this step, the raw materials for each layer prepared in the raw material preparation step are filled into a mold in the order of, for example, the second porous layer / the first porous layer / the dense layer / the first porous layer / the second porous layer, and pressed to obtain pellets. The pressure for the press molding is, for example, 1 Ton / cm. 2 That's about it.
[0039] [Firing process] In this step, the pellets obtained in the molding step are heated, for example, at 400° C. in air to volatilize the cross-linked polymethyl methacrylate and the organic binder, and then fired, for example, at 800° C. in air to obtain a sintered body.
[0040] [Impregnation process] In this step, a substance that provides electrical conductivity is added to the sintered body obtained in the firing step, and the sintered body is impregnated by drying the sintered body, for example, at room temperature, and then drying the sintered body, for example, in a vacuum at about 210° C. Examples of the substance that provides electrical conductivity include a polyimide solution and a dispersion of carbon powder.
[0041] [Re-firing process] In this step, the sintered body obtained in the impregnation step is fired again in nitrogen at about 700° C., for example, to obtain a sintered body having electrical conductors formed in the pores of the porous layer.
[0042] [Current collector formation process] In this step, current collectors are formed on both sides of the sintered body obtained in the re-firing step. The current collectors can be formed by, for example, Au sputtering.
[0043] In this manner, the electricity storage device 1 can be manufactured.
[0044] (summary) As is apparent from the above embodiment, the present disclosure includes the following aspects. In the following, reference symbols are given in parentheses only to clarify the correspondence with the embodiment.
[0045] The electricity storage device (1) according to the first embodiment of the present disclosure is an electricity storage device including a first electrode (11), a second electrode (12), a solid electrolyte layer (20) including a solid electrolyte (Y) and disposed between the first electrode (11) and the second electrode (12), and a conductor (X) disposed in the solid electrolyte layer (20). The solid electrolyte layer (20) includes a dense layer (30) and a porous layer (40) disposed between the dense layer (30) and at least one of the first electrode (11) and the second electrode (12). The porous layer (40) includes a first porous layer (41) in contact with the dense layer (30) and having a higher porosity than the dense layer (30), and a second porous layer (42) in contact with the first porous layer (41) and having a higher porosity than the first porous layer (41).
[0046] According to the first aspect, in the electricity storage device (1), the occurrence of cracks can be suppressed and the capacity can be increased.
[0047] In the electricity storage device (1) according to the second embodiment of the present disclosure, in the first embodiment, the porosity of the dense layer (30) is 10% or less.
[0048] According to the second aspect, it is possible to suppress conduction of the conductor (X) in the dense layer (30), and to prevent the electricity storage device (1) from failing to function as a capacitor.
[0049] In the electricity storage device (1) of the third aspect, in the first or second aspect, the porosity of the first porous layer (41) is 5% or more and 20% or less.
[0050] According to the third aspect, the difference in porosity between the layers of the electricity storage device (1) can be made smaller, and the occurrence of cracks can be further suppressed.
[0051] In the electricity storage device (1) of the fourth aspect, in any one of the first to third aspects, the porosity of the second porous layer (42) is 10% or more and 50% or less.
[0052] According to the fourth aspect, it is possible to achieve both the ease of forming the conductor (X) by impregnation and the strength of the second porous layer (42), and as a result, it is possible to further increase the capacity of the electricity storage device (1).
[0053] In the electricity storage device (1) of the fifth aspect, in any one of the first to fourth aspects, the thickness of the second porous layer (42) is greater than the thickness of the first porous layer (41).
[0054] According to the fifth embodiment, the thickness of the portion having a large porosity can be made larger, and as a result, the capacity of the electricity storage device (1) can be increased.
[0055] In the electricity storage device (1) of the sixth embodiment, the thickness of the first porous layer (41) is not less than 100 μm and not more than 2000 μm.
[0056] According to the sixth aspect, the DCR of the electricity storage device (1) can be further reduced.
[0057] In the electricity storage device (1) of the seventh aspect, in any one of the first to sixth aspects, the second porous layer (42) has a thickness of 100 μm or more and 2000 μm or less.
[0058] According to the seventh aspect, the thickness of the portion with high porosity can be increased, and as a result, the capacity of the electricity storage device (1) can be further increased.
[0059] In the electricity storage device (1) of an eighth aspect, in any one of the first to seventh aspects, a conductive material containing carbon is disposed as the conductor (X) in the pores of the porous layer (40).
[0060] According to the eighth aspect, conductive particles with improved dispersibility can be arranged in the pores of the porous layer (40), and the capacity of the electricity storage device (1) can be further increased.
[0061] In a ninth aspect of the electricity storage device, in any one of the first to eighth aspects, the solid electrolyte (Y) is a Li ion conductor.
[0062] According to the ninth aspect, an all-solid-state capacitor can be formed. EXAMPLES
[0063] Hereinafter, the present disclosure will be specifically described with reference to examples, but the present disclosure is not limited to only these examples.
[0064] <Fabrication of electricity storage device> The electricity storage device (all-solid-state capacitor) of Example 1 was produced by the following procedure. [Preparation of raw materials] The raw materials for forming the dense layer, the first porous layer, and the second porous layer are Li as a solid electrolyte. 1.3 Al 0.3 Ti 1.7 The powder of (PO4)3(LATP) was mixed with cross-linked polymethylmethacrylate in the ratio shown below (mass % relative to the total raw materials), followed by the addition of Li3PO4 as a sintering aid and polyvinyl alcohol as an organic binder. Dense layer: none added (0 mass%), first porous layer: 10 mass%, second porous layer: 30 mass%
[0065] [Molding] The raw materials for each layer prepared above were filled in a cylindrical mold having an inner diameter of 13 mm in the following order: second porous layer / first porous layer / dense layer / first porous layer / second porous layer, and the raw materials were mixed at a density of 1 Ton / cm. 2 The mixture was pressed at a pressure of 1000 to obtain a disk-shaped pellet.
[0066] [Firing] The obtained pellets were heated in air at 400° C. to volatilize the crosslinked polymethyl methacrylate and the organic binder, and then fired in air at 800° C. to obtain a sintered body. In the obtained sintered body, the porosity of each layer was as follows: Dense layer: 0%, 1st porous layer: 9.3%, 2nd porous layer: 19%
[0067] [Impregnation] A few drops of the polyimide solution were dropped onto one side of the obtained sintered body using a dropper, and the body was dried at room temperature in a vacuum dryer. This operation was repeated twice. Then, the body was dried in a vacuum at 210°C. The same operation was carried out on the other side.
[0068] [Re-firing] The impregnated sintered body was fired again at 700° C. in nitrogen to obtain a sintered body in which the polyimide solution was carbonized in the porous layer.
[0069] [Current collector formation] A current collector was formed on both sides of the refired sintered body by Au sputtering. The current collector had a diameter of 10 mm.
[0070] In this manner, an all-solid-state capacitor of Example 1 was produced. Moreover, an all-solid-state capacitor of Comparative Example 1 was produced in the same manner as in Example 1, except that the first porous layer was not provided.
[0071] <Evaluation> [Cyclic voltammetry] The voltage of the fabricated all-solid-state capacitor was swept at 10 mV / s, and the current flowing at that time was measured. The capacitance of the all-solid-state capacitor was calculated from this data. If the area enclosed by the curve plotted with the voltage on the horizontal axis and the current on the vertical axis is S, the capacitance C of the device can be expressed as C = S / 2vV, where v is the voltage sweep speed and V is the voltage sweep width.
[0072] [Impedance measurement] The impedance of the fabricated all-solid-state capacitor was measured at an applied voltage of 10 mV and a frequency of 10 mHz. The real component of the impedance at this time was taken as the DCR.
[0073] The measured capacitance (mF) and DCR (kΩ) are shown in Table 1 below.
[0074] [Table 1]
[0075] SEM analysis of the interface between the porous layer and the dense layer in the all-solid-state capacitor of Comparative Example 1 confirmed that a large crack was present between the layers. As can be seen from the results in Table 1, Comparative Example 1 has a capacity of 1 / 50 times that of Example 1, and a DCR of 22 times. The second porous layer on the outermost surface, which is impregnated with the polyimide solution, has the same porosity. Therefore, the difference in this evaluation is due to the presence or absence of the first porous layer between the second porous layer and the dense layer. In Comparative Example 1, it is presumed that the absence of the first porous layer caused cracks at the interface between the second porous layer and the dense layer, resulting in deterioration of the characteristics. In particular, it is presumed that the polyimide solution impregnated in both electrodes was impregnated up to the dense layer due to the cracks occurring up to the dense layer, resulting in a state close to conduction, resulting in a large decrease in capacity. [Explanation of symbols]
[0076] 1. Energy storage devices 11 First electrode 12 Second electrode 20 Solid electrolyte layer 30 Layer compacta 40 porous layer 41 1st porous layer 42 Second porous layer
Claims
1. A first electrode; A second electrode; and a solid electrolyte layer including a solid electrolyte and disposed between the first electrode and the second electrode; a conductor disposed in the solid electrolyte layer; A power storage device comprising: the solid electrolyte layer has a dense layer and a porous layer disposed between the dense layer and at least one of the first electrode and the second electrode, the porous layer includes a first porous layer in contact with the dense layer and having a porosity higher than that of the dense layer, and a second porous layer in contact with the first porous layer and having a porosity higher than that of the first porous layer. Energy storage device.
2. The porosity of the dense layer is 10% or less. The power storage device according to claim 1 .
3. The porosity of the first porous layer is 5% or more and 20% or less. The power storage device according to claim 1 .
4. The porosity of the second porous layer is 10% or more and 50% or less. The power storage device according to claim 1 .
5. The thickness of the second porous layer is greater than the thickness of the first porous layer. The power storage device according to claim 1 .
6. The thickness of the first porous layer is 100 μm or more and 2000 μm or less. The power storage device according to claim 1 .
7. The thickness of the second porous layer is 100 μm or more and 2000 μm or less. The power storage device according to claim 1 .
8. As the conductor, a conductive material containing carbon is disposed in the pores of the porous layer. The power storage device according to claim 1 .
9. The solid electrolyte is a Li ion conductor. The power storage device according to claim 1 .
Citation Information
Patent Citations
Solid electrolyte structure for all-solid-state battery, all-solid-state battery, and their production methods
WO2008059987A1